2014
DOI: 10.1016/j.rehab.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The motor function measure to study limitation of activity in children and adults with Charcot-Marie-Tooth disease

Abstract: Our results suggest that, especially for D1 and D3 sub-scores, the motor function measure is a reliable and valid outcome measure that can be usefully applied in longitudinal follow-up. Studies of longer duration could demonstrate its responsiveness in other Charcot-Marie-Tooth disease subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
0
9
1
7
Order By: Relevance
“…The SRM of dimensions one (standing and transferring) and three (distal motor function) were considered moderate (SRM = 0.68 and 0.50, respectively) and the total score of the SRM was high (SRM = 0.85). Mean reassessment intervals were much longer than in the present study (27 ± 17 months) 17 . The Motor Function Measure should not be used in intervals shorter than one year to evaluate patients with DMD The present study showed that sit-to-stand and stand-to-sit are more responsive outcome measures.…”
contrasting
confidence: 76%
See 1 more Smart Citation
“…The SRM of dimensions one (standing and transferring) and three (distal motor function) were considered moderate (SRM = 0.68 and 0.50, respectively) and the total score of the SRM was high (SRM = 0.85). Mean reassessment intervals were much longer than in the present study (27 ± 17 months) 17 . The Motor Function Measure should not be used in intervals shorter than one year to evaluate patients with DMD The present study showed that sit-to-stand and stand-to-sit are more responsive outcome measures.…”
contrasting
confidence: 76%
“…Cano et al 28 recommended that the ES should be interpreted with caution and combined with other statistical methods to avoid misinterpretation 28 . Only six studies investigated the responsiveness of one or more tests for neuromuscular diseases 2,16,17,18,19,29 . Most studies used the ES 18 and SRM 2,16,17 in isolation or in combination 19,29 .…”
mentioning
confidence: 99%
“…Nos estudos com doenças neuromusculares, as escalas ACTIVLIM (VANDERVELDE et al, 2009), Medida da Função Motora (VUILLEROT et al, 2012, ALLARD et al, 2014, North Star Ambulatory Assessment (MAYHEW et al, 2013), Medida de Independência Funcional (DE GROOT et al, 2006), Índice de Barthel (DE GROOT et al, 2006) e Rehabilitation Activities Profile (DE GROOT et al, 2006) demonstraram responsividade.…”
Section: Responsividade Dos Instrumentos De Avaliação Nas Doenças Neuunclassified
“…Em outro estudo de Vuillerot et al (2012) sobre a responsividade da escala Medida da Função Motora, porém no seguimento de um ano, observou-se responsividade apenas no grupo com 41 pacientes com distrofia muscular de Duchenne (MRP do escore total de 0,91, domínio um de 0,47, domínio dois de 0,68 e domínio três de 0,30). Já no estudo de responsividade da escala Medida da Função Motora em 102 pacientes com Charcot-Marie-Tooth, foi observada responsividade significante do domínio um (MRP=0,68), do domínio três (MRP=0,50) e do escore total (MRP=0,85) apenas em Charcot-Marie-Tooth do tipo II com 27,3 ± 17 meses entre as avaliações (ALLARD et al, 2014).…”
Section: Responsividade Dos Instrumentos De Avaliação Nas Doenças Neuunclassified
“…Functional capability has been further evaluated in CMT using a validated instrument known as the motor function measure (MFM) that is widely used to assess motor function in neuromuscular disorders. Allard et al, () showed that MFM was both a reliable and valid instrument, which could effectively be used in CMT patients from 4 to 80 years of age. The use of MFM reveals a decline in motor function with age, consistent with the progressive nature of the condition, a decline seen most clearly in “standing positions and transfers” and “distal motor function.” Axial and proximal motor function showed virtually no change, consistent with the known pathology of a peripheral neuropathy.…”
Section: Cinical Featuresmentioning
confidence: 99%